Trade Openness and Spatial Inequality in Developing Countries: Case Study of ASEAN-4 - Violeta, Rosalia Marcha; Sahetapy, Vedy Ardine; Maharsi, Garda; Revindo, Mohamad Dian (Jurnal Kebijakan Ekonomi, 2025)
Trade openness is widely associated with stronger medium- to-long-term economic growth, yet its distributional consequences within countries, particularly in developing economies, remain contested. This paper examines the relationship between trade openness and spatial inequality in four major ASEAN economies, Indonesia, Malaysia, Thailand, and the Philippines, over the period 2012–2019. Spatial inequality is measured using Theil’s Index based on provincial-level GDP per capita, while trade openness is proxied by the trade-to-GDP ratio. Employing pooled OLS and fixed-effects estimations, the analysis controls for key structural factors such as economic development, population size, urbanization, government expenditure, and the number of spatial units. The results indicate that, contrary to much of the prevailing literature, higher trade openness is associated with lower spatial inequality in most model specifications. This finding suggests that, in the ASEAN-4 context, trade integration may generate more geographically inclusive outcomes, potentially reflecting export structures, resource-based production, and labor market dynamics distinct from those in advanced economies. While the results should be interpreted cautiously given data limitations, the study contributes new empirical evidence to debates on trade and inequality in developing regions and highlights the importance of subnational perspectives in assessing the distributive effects of globalization.